Does growth in the outdoors stay in the outdoors? The impact of an extended residential and outdoor learning experience on student motivation, engagement and 21st century capabilities - Mann, Jeff; Gray, Tonia; Truong, Son (Frontiers in Psychology, 2023)
Student motivation and engagement underpin educational success, and recent research has found they are lowest in middle high school, especially for boys. At the same time, education systems are recognising that academic performance is necessary but not sufficient to prepare young people for the adult world, and so-called ‘21st Century skills’ (communication, collaboration, critical thinking and creativity) have been suggested as critical capabilities across all employment sectors in the future. The Glengarry program is a six-month residential and outdoor learning experience for Year 9 (14-15 years old) boys at an Australian private school, The Scots College (TSC) Glengarry. Intentionally located during the lowest point of engagement in their adolescent student journey, the Residential and Outdoor Education experience was hypothesised to boost their motivation and engagement and develop 21st Century skills. The Glengarry program involves students living in a boarding-style community for 20 weeks away from their families, participating in classes across all regular school subjects at a bush campus, and undertaking increasingly challenging outdoor education trips each week. The study aimed to measure how these factors transferred into students’ traditional school environment after their Glengarry experience. Year 9 was split into two cohorts who both participated in the study: one of which completed the Glengarry program in the first half of 2019, and the other during the second half of the year. Self-reported quantitative and qualitative data supported the hypothesis that the Glengarry program did indeed, boost student motivation and 21st Century skills. Whilst gains in 21st Century skills endured over the next 8-10 months, motivation and some engagement factors decreased upon return to the traditional school environment. Students described key factors in the Glengarry program which facilitated their development, including: an intense residential environment necessitating social growth, a closer connection with teachers in both school and community life, and an appreciation of learning in the natural environment. Recommendations are made for future research to strengthen these findings, and for how these mediating factors could be incorporated into the regular school environment.